Film Properties of Heparin Cross-Linked with Epichlorohydrin in Absence or Presence of Imidazole - Ivan Šimkovic; Filip Gucmann; Michal Hricovíni; Raniero Mendichi; Edmund Dobročka; Alberto Giacometti Schieroni; Daniele Piovani; Stefania Zappia; Miloš Hricovíni (Polysaccharides)
We cross-linked unfractionated heparin (H) using epichlorohydrin (E), in the absence or presence of imidazole (I), using various ratios of H, E, and I substances. The objectives and goals were to use the reaction for the preparation of medical materials suitable for blood sample applications. Nuclear magnetic resonance indicated the involvement of an H-end sequence [H-(1→4)-β-D-GlcA-(1→3)-β-D-Gal-(1→3)-β-D-Gal-(1→4)-β-D-Xyl-α-Ser] in the linkage with the 2-hydroxypropyl bridge. The yields of the individual experiments were found to increase in the following ratios: 1H/1E/3I (24%) < 1H/1E/2I (32%) < 1H/3E (42%) < 1H/1E/1I (46%) < 1H/2E (64%) < 1H/1E (77%). According to size-exclusion chromatography with multiple-angle light scattering (SEC-MALS) analysis, the mass at the peak increased in the following order: H (9292 g/mol) < 1H/1E (9294 g/mol) < 1H/2E (9326 g/mol) < 1H/3E (9708 g/mol) < 1H/1E/2I (11,212 g/mol) < 1H/1E/3I (12,301 g/mol) < 1H/1E/1I (13,800 g/mol) and in the reverse order with the increase in amount of epichlorohydrin and imidazole, i.e., 1H/1E > 1H/2E > 1H/3E and 1H/1E/1I > 1H/1E/2I > 1H/1E/3I. X-ray diffraction revealed that all prepared films were amorphous. An evaluation of the surface morphology using atomic force microscopy (AFM) confirmed a relatively low films roughness (~0.9–3.6 nm). The surface reduced elastic modulus, determined by the PeakForce quantitative nanomechanical mapping (PF-QNM) technique, was found to increase by up to ~63% for films cross-linked with E in the absence of I when compared with the results for the H substrate. A negligible change in modulus was, however, observed for films cross-linked in the presence of I, or was even reduced by ~15% (1H/1E/3I) compared to that for the H substrate. This could be explained by the parallel cross-linking of H only with E within its serine end unit and in competition with only one nitrogen of I. According to the highest yield (77%) of 1H/1E, the preferred product is the following: H-(1→4)-β-D-GlcA-(1→3)-β-D-Gal-(1→3)-β-D-Gal-(1→4)-β-D-Xyl-α-Ser-CH2-CH(OH)-CH2-OH. For the 1H/1E/1I (46% yield), 1H/1E/2I (32%), and 1H/1E/3I (24%) products, the cross-linked motif was the same, and the difference represented the surplus amount of the imidazolium cation ionically bound to the heparin anionic groups.